VD_FINDINFO Pron / 2012 / 198 vom 10. September 2012 - VD Tribunal cantonal (2012)
REPRÉSENTATION, ASSISTANCEEN GÉNÉRAL, MANDATAIRE | 204 al. 2 CPC (CH), 319 let. b ch. 2 CPC (CH), 68 al. 2 CPC (CH), 11 LJB